An integrative lean assessment model for distribution centres - Mahfouz, Amr; Smith, Laura; Arisha, Amr (Cranfield University Press, 2013)
It is hard to benefit fully from lean manufacturing without having an efficient distribution centre. Applying lean distribution concept helps to reduce distribution centres waste while maintains customer service level high. The purpose of this study is to develop a lean assessment model that enables distribution managers to measure and improve the leanness levels of their companies. A data driven analytical approach (i.e. factor analysis) is used to assess leanness quantitatively. A lean index score is calculated to benchmark the leanness level of four distribution companies based in Ireland and UK. Results recommend that special attention should be taken on simplifying distribution network structure, establishing long term suppliers’ collaboration, managing customer demand, improving storage space utilisation, and managing distribution operations more efficiently.
Keywords: Lean Distribution; Lean Assessment; Factor Analysis